Sustainability Disclosures, Environmental Investments, and Corporate Valuation: Examining the Interplay between Performance and Perception - Komang Suci Purnami; Luh Gede Krisna Dewi (E-Jurnal Akuntansi, 2025)
Firm value represents the market’s assessment of a company’s overall worth, often proxied through its share price and the volume of outstanding shares traded on the capital market. This study investigates the extent to which sustainability performance, environmental costs, and environmental performance influence firm value. The empirical analysis draws on a panel of 44 energy and mining firms listed on the Indonesia Stock Exchange over the 2019–2023 period, yielding a total of 178 firm-year observations. The findings reveal a significant negative association between sustainability performance and firm value, suggesting that market participants may interpret sustainability-related disclosures or initiatives as costly or misaligned with immediate financial performance. In contrast, environmental costs demonstrate a statistically significant positive relationship with firm value, implying that proactive environmental spending may signal responsible risk management or long-term strategic investment. However, environmental performance was not found to exert a statistically significant influence on firm value. These results underscore the nuanced manner in which capital markets interpret sustainability-related activities. For investors and other stakeholders, sustainability performance—despite its growing importance in corporate discourse—may warrant critical scrutiny in terms of its perceived value-adding potential.